The ancient Britons: groundwater fauna survived extreme climate change over tens of millions of years across NW Europe. Issue 5 (20th February 2014) - McInerney, Caitríona E.; Maurice, Louise; Robertson, Anne L.; Knight, Lee R. F. D.; Arnscheidt, Jörg; Venditti, Chris; Dooley, James S. G.; Mathers, Thomas; Matthijs, Severine; Eriksson, Karin; Proudlove, Graham S.; Hänfling, Bernd
Abstract Global climate changes during the Cenozoic (65.5–0 Ma) caused major biological range shifts and extinctions. In northern Europe, for example, a pattern of few endemics and the dominance of wide‐ranging species is thought to have been determined by the Pleistocene (2.59–0.01 Ma) glaciations. This study, in contrast, reveals an ancient subsurface fauna endemic to Britain and Ireland. Using a Bayesian phylogenetic approach, we found that two species of stygobitic invertebrates (genus Niphargus) have not only survived the entire Pleistocene in refugia but have persisted for at least 19.5 million years. Other Niphargus species form distinct cryptic taxa that diverged from their nearest continental relative between 5.6 and 1.0 Ma. The study also reveals an unusual biogeographical pattern in the Niphargus genus. It originated in north‐west Europe approximately 87 Ma and underwent a gradual range expansion. Phylogenetic diversity and species age are highest in north‐west Europe, suggesting resilience to extreme climate change and strongly contrasting the patterns seen in surface fauna. However, species diversity is highest in south‐east Europe, indicating that once the genus spread to these areas (approximately 25 Ma), geomorphological and climatic conditions enabled much higher diversification. Our study highlights that groundwater ecosystems provide an important contribution to biodiversity and offers insight into the interactions between biological and climatic processes.